Status Karies Gigi pada Pengidap HIV/AIDS - Sundah, Michael J.; Mintjelungan, Christy N.; Pangemanan, Damajanty H. C. (e-GiGi, 2021)
Abstract: Human immunodeficiency virus (HIV) is a virus that attacks the human immune system, especially white blood cells called CD4 cells. Meanwhile, acquired immune deficiency syndrome (AIDS) is a syndrome that arises due to the decline in the human immune system caused by HIV infection. Several studies showed that people living with HIV/AIDS had a higher risk of developing dental caries compared to those without HIV/AIDS. Maintenance of oral hygiene, consumption of antiretroviral (ARV) drugs, and low salivary flow play a role in increasing the risk of caries in people living with HIV/AIDS. This study was aimed to determine the status of dental caries in people living with HIV/AIDS. This was a literature review using the databases of Google Scholar, PubMed, and Clinical Key. The results obtained five journals that were relevant to the topic of discussion. There was a high prevalence of caries in people with HIV/AIDS (56.78%-78.7%) and a higher average caries status (12.83±9.6, 15.14±6.09, and 11.87±8.08) compared to those without HIV/AIDS. The high prevalence of caries in people with HIV/AIDS was influenced by decreased salivary flow, use of ARVs, consumption of sweet foods, and lack of oral hygiene. In conclusion, the prevalence of caries in people living with HIV/AIDS was high.Keywords: dental caries, HIV/AIDS  Abstrak: Human immunodeficiency virus (HIV) adalah virus yang menyerang sistem kekebalan tubuh manusia kususnya sel darah putih yang disebut sel CD4 sedangkan acquired immune deficiency syndrome (AIDS) merupakan sindrom yang muncul akibat menurunnya sistem kekebalan tubuh manusia yang diakibatkan infeksi HIV. Beberapa penelitian menunjukkan bahwa pengidap HIV/AIDS berisiko lebih tinggi mengalami karies gigi dibandingkan dengan orang tanpa HIV/AIDS. Pemeliharaan kebersihan gigi mulut, konsumsi obat antiretroviral (ARV), dan aliran saliva yang rendah berperan dalam peningkatan risiko karies gigi pada pengidap HIV/AIDS. Penelitian ini bertujuan untuk mengetahui status karies gigi pada pengidap HIV/AIDS. Jenis penelitian ialah suatu literature review. Database yang digunakan untuk pencarian literatur ialah Google Scholar, PubMed, dan Clinical Key. Hasil penelitian mendapatkan prevalensi karies yang tinggi pada pengidap HIV/AIDS (56,78%-78,7%) dan rerata status karies lebih tinggi (12,83±9,6, 15,14±6,09, dan 11,87±8,08) dibandingkan dengan yang tanpa HIV/AIDS. Tingginya prevalensi karies pada pengidap HIV/AIDS dipengaruhi oleh penurunan laju aliran saliva, penggunaan ARV, konsumsi makanan manis, dan kurangnya menjaga kebersihan gigi mulut. Simpulan penelitian ini ialah prevalensi karies pada pengidap HIV/AIDS tergolong tinggi.Kata kunci: karies gigi, HIV/AIDS